2021
DOI: 10.1111/dth.14736
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pyoderma gangrenosum: A multicenter survey‐based study assessing satisfaction and quality of life

Abstract: Pyoderma gangrenosum (PG) lacks consensus regarding treatment, and no prior studies assess treatment satisfaction in PG. The objective of this study was to determine patient-reported satisfaction in the treatment of PG, and associations with satisfaction. Methodology was a multicenter cross-sectional survey for patients who received systemic medication(s) to treat PG. Thirty-five patients completed the survey (mean age: 54.0 years, 65.7% female, response rate: 81.4%). Mean (± SD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A recent survey of patients with PG found that nearly one-third had an educational level of a high school diploma equivalent or less ( Hobbs et al, 2021 ), highlighting that patients with PG may have difficulty comprehending more than half of the websites in this study. Articles written at a higher grade level were not associated with higher content quality.…”
mentioning
confidence: 79%
“…A recent survey of patients with PG found that nearly one-third had an educational level of a high school diploma equivalent or less ( Hobbs et al, 2021 ), highlighting that patients with PG may have difficulty comprehending more than half of the websites in this study. Articles written at a higher grade level were not associated with higher content quality.…”
mentioning
confidence: 79%
“…Oral immunosuppressants are used in severe cases. Prednisolone is used in first line at a dose of 0.5-1mg /kg/day, the other options include: Cyclosporine, Azathioprine, Methtexate and Inflixumab [4] [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…1,6 First-line treatment is systemic corticosteroids (oral prednisone 0.5-1 mg/kg per day), especially for progressive, severe, or disfiguring disease. 7 Intralesional steroid therapy is less effective (34%) and, in some instances, may worsen PPG lesions due to the induction of pathergy as a result of injection trauma. 2 Cyclosporine (2.5-5 mg/kg per day) is frequently used as a second-line treatment and may be effective, especially in corticosteroid-resistant cases.…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment is systemic corticosteroids (oral prednisone 0.5-1 mg/kg per day), especially for progressive, severe, or disfiguring disease 7. Intralesional steroid therapy is less effective (34%) and, in some instances, may worsen PPG lesions due to the induction of pathergy as a result of injection trauma 2.…”
Section: Discussionmentioning
confidence: 99%